RANCAN BANGUN SISTEM E-VOTING MENGGUNAKAN PROTOKOL TWO CENTRAL FACILITIES - Muharram, Asep Taufik; Satrya, Fitrah (Jurnal Informatika, 2015)
General election of regional head, governor or regent, in Indonesia is conducted conventionally. This kind of election is prone of human errors and also black campaigns committed by certain parties. This research aims to build an e-voting system in Tasikamalaya City using Two Central Facilities Protocol, i.e.: Central Legitimization Agency (CLA), for the approval of voters, and Central Tabulating Facility (CTF) for counting. This system is purposed to facilitate the general elections, so that the election will be run effectively and efficiently. However, there are some factors to be considered to polish the system in order to implement it in real general elections. Keywords: E-voting, Protocol Two Central Facilities, Tasikmalaya General Election